Medium supplementation with magnesium prevented the induction of dormancy in biofilms of clinical and commensal isolates of Staphylococcus epidermidis - Pérez-Cabezas, B. (2013)
Staphylococcus epidermidis is a commensal bacterium that colonizes the skin and mucous membranes, being the most prevalent staphylococcal species found in humans. However, S. epidermidis has the ability of colonize indwelling medical devices establishing biofilms, which makes this bacteria a common cause of bacteraemia particularly in immunocompromised individuals and neonates [1][2]. The presence of high amounts of dormant bacteria (viable but non-culturable cells, VBNC) is a hallmark of biofilms, making them more tolerant to antimicrobials and elusive to the host immune response [3]. Glucose (G) is commonly used in vitro to induce a biofilm mode of growth in S. epidermidis cultures [4] due to the medium acidification derived from carbon metabolism [5]. Previous studies in our laboratory demonstrated that the accumulation of VBNC bacteria inside S. epidermidis biofilms could be prevented by supplementation of the medium with magnesium (Mg) (unpublished data). In the present work, a flow cytometric live/dead staining [6], in combination with the spreadplate method, were used to evaluate the effect of magnesium in preventing dormancy on glucose excess-grown biofilms in 53 strains of international clinical, Portuguese clinical, and Portuguese commensal isolates of S. epidermidis. Culture supplementation with Mg2+ prevented the accumulation of death bacteria inside the biofilms in all the groups of strains tested, being the proportion of live bacteria (SYBR+PI-) significantly increased by Portuguese clinical isolates. The quantification of colony forming units (CFUs) revealed that Mg hampered the induction of dormancy in all the groups of strains studied (International clinical G: 3,60,8×107 vs. G+Mg: 2,60,5×108, Portuguese clinical 6,82,0×107 vs. 4,31,4×108, Portuguese commensal 7,21,5×107 vs. 2,60,4×108 CFUs/mL). These results confirmed that dormancy modulation is widespread in different S. epidermidis isolates obtained from clinical and commensal sources, suggesting that this is indeed an important mechanism of S. epidermidis biofilm physiology.